Orthodontic management of missing maxillary lateral incisors: A case report - Chaudhary, Nabin Kumar; Giri, Jamal; Gyawali, Rajesh; Pokharel, Prabhat Ranjan; Chaudhary, Gyanendra (Orthodontic Journal of Nepal, 2022)
The agenesis of maxillary lateral incisors affects the Quality of Life and self-esteem of patients. The management of such patients can be done by either opening the space and replacing it with the prosthesis or closing the space and substituting the canine as a lateral incisor. The choice of treatment decision depends upon the proper diagnosis and treatment planning of the case. In this case report, a skeletal class II patient with dental diagnosis Angle’s class II malocclusion and spacing in the maxillary arch due to missing lateral incisors is presented with the chief complaint of gap in the upper front region of jaw which is effectively treated with orthodontic space closure followed by a restorative procedure.